Hegemoni Barat dan Islam terhadap Estimasi HAM - Nurkhalis Nurkhalis (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Western human rights based on the dimensions of humanity tha the Islamic Human Rights form fascinating mix between the rights and obligations to each other. There are concrete boundaries between human rights (ẖuqûq al-‘ibâd) and divine rights (ẖuqûq Allâh). Islam encompasses freedom rights that are free value (neutral) does not  violate the devine law and human law that acts between the permissible and the forbidden deeds to be classified in laghâ (in vain) including lâ‘ibun (fun), lahwun (filling time),  tala‘ub amr (command abandoned), and tathawu‘ (motivation goodness). The different- ces between Islam and Western human rights which its is anthropocentric and egocentric, and Islam is theocentric and laghâsentric. Laghâsentric can be defined as an act or behavior in which individuals have the freedom to choose an action object that does not carry a penalty